Environmental cadmium exposure: a possible factor in the pathogenesis of preeclampsia - Nwobi, Nnenna L.; Owolabi, Joshua O.; Sotunsa, John O.; Nwobi, Joseph C.; Abiodun, Razaq A.; Anetor, John I. (International Journal of Research in Medical Sciences, 2019)
Cadmium is a toxic metal, an environmental contaminant and a multi-organ poison which has been implicated in the derangement of a number of biological and molecular systems. Exposure to cadmium is a serious global health threat particularly in developing countries and pregnant women are at great risk, This is because they have increased gastrointestinal absorption and retention of cadmium and the tendency for increased risk of complications owing to its toxic effects. Preeclampsia is a pregnancy complication characterized by the development of onset of hypertension and significant proteinuria after 20 weeks of gestation or during labour and/or within 48 hours of delivery. This pregnancy-specific syndrome is a leading cause of maternal death particularly in developing countries. Several reports have provided evidence of remote association between preeclampsia and cadmium but the mechanism of the involment of this toxic metal in this disease is still surrounded with uncertainty. Some possible mechanistic pathways such as induction of oxidative stress, acting as an antimetabolite to zinc and deregulation of epigenetic mechanisms have been elucidated in this article may be interconnected, work synergistically or act independently. However, pertinent to understand them in a bid to possibly prevent the disease or forestall its devastating consequences. Environmental cadmium exposure may be considered a factor that merits further serious attention in the continuous search for the precise an etiology of preeclampsia particularly in developing countries that experience uncontrolled cadmium release into the environment.